(untitled) (Journal of Medicine, 2021)
Introduction: Nonalcoholic fatty liver disease (NAFLD) is an increasingly recognized cause of liver disease worldwide. The present study was conducted with the aim to determine the association between anthropometric measurement and incidence of NAFLD among the adult population. Material and Methods: A hospital based cross sectional study was performed among 240 patients attending outpatient department of Hepatology, Gastroenterology and admitted in patient of Medicine, Hepatology, Gastroenterology department of Dhaka Medical College Hospital, who are Ultrasound diagnosed NAFLD, fulfilled the inclusion criteria. The Study was done from August, 2013 to February, 2014 in Dhaka Medical College Hospital, Dhaka, Bangladesh. Then a pro-forma was made and filled it by direct interview, reading the remarks of the consultant about the patient written on the file, using the hospital lab results and by discussing the patient’s file remarks with the medical officer on duty. NAFLD was confirmed by Ultrasonography. Relevant Laboratory investigations were done to assess severity and prognosis. All subjects underwent anthropometric measurement which included height, weight, waist circumference, waist hip ratio (WHR), waist height ratio (WHtR). Body mass index (BMI) and were calculated using the standard formula. Results: Out of 240 patients, 51(21.25%) were found to be diagnosed with NAFLD (95%CI=22.8-27.8) subjects. The cases of NAFLD were significantly higher in males (55.0%) as compared to females (45%) (RR=1.17, 95%CI=1.14-2.58, p=0.008). The BMI, waist circumference, WHR and WHtR were significantly (p<0.0001) associated with NAFLD. Likewise, NAFLD was found significantly (p<0.0001) higher among obese and overweight subjects. However, in multivariate logistic regression analysis, sex (adjusted OR=11.30, 95%CI=3.44-37.11, p<0.0001), waist circumference (adjusted OR=1.27, 95%CI=1.56-1.39, p<0.0001), hip circumference (adjusted OR=0.90, 95%CI=0.82-0.99, p=0.04) and BMI (adjusted OR=1.83, 95%CI=1.10- 2.20, p=0.001) were significantly associated with NAFLD. Conclusion: It can be concluded that higher anthropometric measurements were significantly associated with NAFLD. J MEDICINE JAN 2021; 22 (1) : 27-32